2009
DOI: 10.1088/0031-9155/54/5/015
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry considerations for electrical stun devices

Abstract: Electrical dosimetry issues are discussed in relation to electrical stun devices (ESDs). A measure of effectiveness is based on a 'threshold factor,' F(T), calculated with a myelinated nerve model that simulates stimulation of a reference-case neuron (20 microm diameter, 1 cm distant). Several ESDs were measured in the laboratory using resistive loads of 100-1000 Omega; some included air gaps bridged via an electric arc. Conducted current waveform parameters and the associated threshold factors depend on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…We used the stimulation safety factor (SSF), i.e., the ratio between E 50 and E T , to evaluate this relationship. SSF was calculated as the "safety factor" (Oliveira et al 2008) and the "threshold factor" (Reilly et al 2009) but considering as reference the E T of each cell instead of a reference-case neuron. SSF gives a numerical rating that provides a measure of effectiveness to any form of electrical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…We used the stimulation safety factor (SSF), i.e., the ratio between E 50 and E T , to evaluate this relationship. SSF was calculated as the "safety factor" (Oliveira et al 2008) and the "threshold factor" (Reilly et al 2009) but considering as reference the E T of each cell instead of a reference-case neuron. SSF gives a numerical rating that provides a measure of effectiveness to any form of electrical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements confirmed that delivered pulses depend on load impedance (Ben-Yaakov 2006, Reilly et al 2009. Their amplitude and time course may vary considerably.…”
Section: Resultsmentioning
confidence: 66%
“…Their amplitude and time course may vary considerably. Between 500 and 11 200 the electric charge varied from 108 to 30 μC which is about two orders of magnitudes higher than the threshold charge 0.67 μC for nerval stimulation by short pulses (Reilly et al 2009). Overall, load resistances varied between 170 and 3600 and increased nonlinearly with increasing electrode separation distances.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…One can directly measure the current waveform for electric stimulation and the dB/dt waveform for magnetic stimulation. If these waveforms depart significantly from ideal square waves, it is necessary to analyze the possible impact of the waveform distortions, as suggested in Reilly (2009).…”
mentioning
confidence: 99%